A note on a result of Singh and Kulkarni. (15th February 2000) - Fang, Mingliang
Abstract : We prove that iff is a transcendental meromorphic function of finite order and∑ a ≠ ∞ δ ( a, f ) + δ ( ∞, f ) = 2, thenK ( f ( k ) ) = 2 k ( 1 − δ ( ∞, f ) ) 1 + k − k δ ( ∞, f ), whereK ( f ( k ) ) = lim r → ∞ N ( r, 1 / f ( k ) ) + N ( r, f ( k ) ) T ( r, f ( k ) ) This result improves a result by Singh and Kulkarni.